A Hashin‐Shtrikman type semi‐analytical homogenization procedure. Issue 1 (18th November 2019) - Jaworek, David; Gierden, Christian; Waimann, Johanna; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: Heterogeneous materials are important for a vast amount of applications e.g. in automotive industry or in aerospace. For instance when producing components, it can be desired to use materials with a heterogeneous microstructure in order to achieve specific material properties. Thus, it is beneficial to take the materials' microscopic structure into account and couple its behavior to the macroscopic response. As multiscale methods (e.g. FE 2, FE‐FFT) are computationally expensive, semi‐analytical homogenization procedures are investigated to account for the transition between different length scales. In this work, the focus lies on applying a Hashin‐Shtrikman type method to elasto‐plasticity.